Analysis of failure of Illiza Saaduddin djamal on city elections banda aceh in 2017 - shahibul izar; effendi hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRACTOn the 2017 Elections of Banda Aceh Mayor, Illiza Saaduddin Djamal and her partner received 32.23% while her opposition, Aminullah Usman and his partner received 66.27%. This lost was poled from all districts in Banda Aceh, while in fact she had been on the administration and was popular among the communities. In fact, a survey before the election relealed that her electability is quite high compared to her opposition.This study aims to discuss about the factors that caused Illiza defeat on the 2017 Banda Aceh Election. It also aims to find out the reasons the votes did not vote for Illiza any longer. The approach used for this study was mixed method which is a combination of qualitative method for primary data and quantitative method for secondary data.The study shows that Illiza failed in the election because 77% public was unsatisfied during Illiza administration especially on account of water service. Besides that, the study also finds that her proposed visions and missions did not meet the needs and condition of Banda Aceh voters who were more pragmatic at the time. The other factor revealed from the study is that 73% voters became uninterested to her while 54% of voters on the account of gender issue. Moreover, it shows that 68% of the voters switch their support to Aminullah Usman.It is concluded that Illiza lost because Banda Aceh people were unsatified with her administration, for example in water system. They favor Aminullah Usman more because he wants to improve this situation. Moreover, they do not favor Illiza administration any longer. The result also shows that these people of Banda Aceh were influenced by the issue that women cannot lead in the political administration.it is suggested that for the upcoming candidates to prepare their visions and program that the public needs at the time. As for candidate team, they need to anticipate issues that will weaken the poling of the candidate. Illiza Saaduddin Djamal, Failure, Pragmatism.